2022
DOI: 10.1136/gutjnl-2021-325272
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced infiltration of neutrophils promotes pancreatic cancer metastasis via Gas6/AXL signalling axis

Abstract: ObjectivePancreatic ductal adenocarcinoma (PDAC) is a highly metastatic disease and cytotoxic chemotherapy is the standard of care treatment for patients with advanced disease. Here, we investigate how the microenvironment in PDAC liver metastases reacts to chemotherapy and its role in metastatic disease progression post-treatment, an area which is poorly understood.DesignThe impact of chemotherapy on metastatic disease progression and immune cell infiltrates was characterised using flow and mass cytometry com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…This desmoplastic reaction is heterogeneous throughout the tumour and alters tissue stiffness in a spatially distinct manner which can also influence tumour cell dissemination [ 11–13 ]. Recent studies in PDAC and other cancers have shown that standard-of-care chemotherapy can have unintentional side effects on the stroma, for example, by triggering a chemotherapy-induced wound or fibrotic reaction leading to enhanced fibrosis and tumour stiffness, which is thought to further protect cancer cells from treatment [ 5 , 6 , 14 , 15 ]. This can lead to a vicious cycle of increased fibrosis and decreased response to standard-of-care chemotherapy [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This desmoplastic reaction is heterogeneous throughout the tumour and alters tissue stiffness in a spatially distinct manner which can also influence tumour cell dissemination [ 11–13 ]. Recent studies in PDAC and other cancers have shown that standard-of-care chemotherapy can have unintentional side effects on the stroma, for example, by triggering a chemotherapy-induced wound or fibrotic reaction leading to enhanced fibrosis and tumour stiffness, which is thought to further protect cancer cells from treatment [ 5 , 6 , 14 , 15 ]. This can lead to a vicious cycle of increased fibrosis and decreased response to standard-of-care chemotherapy [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that AXL and its ligand GAS6 were highly expressed in many malignant tumors not only in lung cancer. AXL could bind to GAS6 and activate multiple pathways and participate in multiple processes of tumorigenesis, including regulating tumor cell growth, proliferation, migration, invasion and enhancement angiogenesis, etc [24] . Studies also showed that AXL was associated with resistance in patients to antitumor chemotherapy drugs (such as paclitaxel and cisplatin) or molecularly targeted drugs (such as erlotinib and gefitinib) [25] , [26] , [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Then, neutrophil-derived Gas6 induces AXL Receptor Tyrosine Kinase (AXL) on metastatic tumor cells and finally contributes to metastatic growth in liver. Furthermore, the pharmacological targeting of the Gas6/AXL axis through warfarin in combination with gemcitabine treatment suppresses metastatic relapse ( 76 ). Another latest study has revealed that IL-17-mediated neutrophil infiltration contributes to gastric tumor angiogenesis and maintains tumor persistence ( 77 ).…”
Section: Neutrophils In Cancer Progressionmentioning
confidence: 99%